MOLEonline 2.0: interactive web-based analysis of biomacromolecular channels - Berka, Karel; Hanák, Ondrej; Sehnal, David; Banás, Pavel; Navrátilová, Veronika; Jaiswal, Deepti; Ionescu, Crina-Maria; Svobodová Vareková, Radka; Koca, Jaroslav; Otyepka, Michal (Nucleic acids research, 2012)
Biomolecular channels play important roles in many biological systems, e.g. enzymes, ribosomes and ion channels. This article introduces a web-based interactive MOLEonline 2.0 application for the analysis of access/egress paths to interior molecular voids. MOLEonline 2.0 enables platform-independent, easy-to-use and interactive analyses of (bio)macromolecular channels, tunnels and pores. Results are presented in a clear manner, making their interpretation easy. For each channel, MOLEonline displays a 3D graphical representation of the channel, its profile accompanied by a list of lining residues and also its basic physicochemical properties. The users can tune advanced parameters when performing a channel search to direct the search according to their needs. The MOLEonline 2.0 application is freely available via the Internet at http://ncbr.muni.cz/mole or http://mole.upol.cz.
Keywords: Enzymes; Ribosome Subunits, Large, Archaeal; Cytochrome P-450 CYP3A; počítačová grafika; User-Computer Interface; Ribosomes; Ion Channels; internet; molekulární modely; ribozomy; Software; Protein Conformation; software; konformace proteinů; enzymy; velké podjednotky ribozomu archebakteriální; cytochrom P-450 CYP3A; uživatelské rozhraní počítače; Computer Graphics; Internet; Models, Molecular; iontové kanály